2017
DOI: 10.3390/nu9121279
|View full text |Cite
|
Sign up to set email alerts
|

Dose-Dependent Effects of Oral Tyrosine Administration on Plasma Tyrosine Levels and Cognition in Aging

Abstract: The effects of tyrosine on plasma response and cognition in aging are unknown. We assessed the dose-dependent response to tyrosine administration in older adults in both plasma tyrosine concentrations and working memory performance. In this double blind randomized cross-over trial 17 older adults (aged 60–75 years) received a single administration of 100, 150, or 200 mg/kg body weight of tyrosine. For comparison, 17 young adults (aged 18–35 years) received a dose of 150 mg/kg body weight of tyrosine. Tyrosine … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
26
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 31 publications
(28 citation statements)
references
References 45 publications
1
26
1
Order By: Relevance
“…A study in adult schizophrenia patients (mean age 37.8 years, SD 6.8) displayed increased errors in a smooth pursuit saccades task in eight patients during three weeks supplementation of 10-g tyrosine daily (Deutsch et al, 1994). In line with an overdose hypothesis, a recent study demonstrated decreased working memory (i.e., n-back) performance with increasing tyrosine dose (from 100-150 to 200 mg/kg) in older adults (aged 60–75 years, mean age: 69.6; van de Rest et al, 2017). This cognitive overdose effect of tyrosine, which has so far been observed only in older adults, may be at least partly caused by a larger effective dose in older adults due to increased peripheral supply of tyrosine.…”
Section: Discussionmentioning
confidence: 75%
See 3 more Smart Citations
“…A study in adult schizophrenia patients (mean age 37.8 years, SD 6.8) displayed increased errors in a smooth pursuit saccades task in eight patients during three weeks supplementation of 10-g tyrosine daily (Deutsch et al, 1994). In line with an overdose hypothesis, a recent study demonstrated decreased working memory (i.e., n-back) performance with increasing tyrosine dose (from 100-150 to 200 mg/kg) in older adults (aged 60–75 years, mean age: 69.6; van de Rest et al, 2017). This cognitive overdose effect of tyrosine, which has so far been observed only in older adults, may be at least partly caused by a larger effective dose in older adults due to increased peripheral supply of tyrosine.…”
Section: Discussionmentioning
confidence: 75%
“…This cognitive overdose effect of tyrosine, which has so far been observed only in older adults, may be at least partly caused by a larger effective dose in older adults due to increased peripheral supply of tyrosine. Earlier research demonstrated increased plasma tyrosine levels in fasting older versus young women (Caballero et al, 1991) and increased plasma response in older versus young adults receiving the same dose (van de Rest et al, 2017). Critically, in this latter study, dose-dependent increases in plasma response correlated with dose-dependent decrements in working memory after tyrosine ingestion.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Aging is accompanied by deficits in inhibitory functions, both in terms of the inhibition of irrelevant information, e.g., sensory suppression (Gazzaley et al, 2008;Healey et al, 2008), as well as in terms of response inhibition, such as in stop-signal tasks (Kramer et al, 1994;Bedard et al, 2002;van de Laar et al, 2011). Two forms of response inhibition have been distinguished: reactive response inhibition is the process of canceling an ongoing response at the moment this is needed (i.e., outright stopping), whereas proactive response inhibition entails the preparation for stopping when this may become necessary, e.g., based on cues held in working memory.…”
Section: Introductionmentioning
confidence: 99%